PARTNERSHIP STRATEGY AS AN EFFORT FOR ECONOMIC EMPOWERMENT TO ENHANCE THE ECONOMY OF TOBACCO FARMERS: A PERSPECTIVE OF FIQH MUAMALAH AT PT. SADHANA JEMBER - Juhairiyah; Abdul Rokhim, Nikmatul Masruroh (Adisam Publisher, 2024)
The aim of this research is to explore the partnership strategies implemented by PT. Sadhana Jember to enhance the economic status of tobacco farmers and the partnership patterns at PT. Sadhana Jember from the perspective of fiqh muamalah. The research methodology employed is qualitative research. Data collection techniques include observation, interviews, and documentation. The data analysis technique utilized is qualitative data analysis employing triangulation methods including data reduction, data display, and conclusion drawing. The findings reveal that PT. Sadhana Jember's partnership strategy, known as the Core-Plasma pattern, prioritizes partners as the core and the company as the plasma. This strategy involves internal identification, partner selection, and agreement establishment. The welfare impacts encompass meeting basic needs and spiritual fulfillment, reflecting a comprehensive approach. From a fiqh muamalah standpoint, Mudharabah and Musyarakah financing models propel agricultural development, particularly in tobacco farming, instilling economic awareness and benefiting landowners through profit-sharing arrangements, consequently elevating their living standards.